PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) PADA MATERI SATUAN PANJANG - Mayuri Putri, Iftisan Sundari; Amri, Salim; Anggraini, Reri Seprina (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2024)
One approach to mathematics in learning activities at school is the Indonesian realistic mathematics education approach or what is known as PMRI/RM. The aim of this research is to find out how realistic mathematics education is applied to length unit material. The research method used is descriptive qualitative. The subjects of this research were class IV students at SDN O63/XI Koto Padang. Data collection techniques are observation, documentation and interviews. Based on research, it was found that students in class IV at SDN 063/XI Koto Padang were able to understand length units by using a realistic mathematical approach.